Gut bacteriome, mycobiome and virome alterations in rheumatoid arthritis - Dagar, Sonali; Singh, Jagdeep; Saini, Aastha; Kumar, Yashwant; Chhabra, Seema; Minz, Ranjana Walker; Rani, Lekha (Frontiers in Endocrinology, 2023)
Rheumatoid arthritis (RA) is a chronic destructive autoimmune disease of the joints which causes significant pain, functional disability, and mortality. Although aberrant immune cell activation induced by the imbalance between T helper Th1/ Th17 and Treg cells is implicated in the RA development, its etiopathogenesis remains unclear. The presence of mucosal inflammation and systemic IgA-isotype-autoantibodies (anti-citrullinated peptide antibodies and rheumatoid factor) in pre-clinical RA supports the mucosal origin hypothesis involving altered microbiota in disease development. The gut microbiota comprises diverse bacteria, fungal and viral components, which are critical in developing host immunity. Alterations in microbial abundance are known to exacerbate or attenuate immune responses in the gut microenvironment subsequently affecting the joints. Further, these changes can provide biomarkers for disease activity and outcome in RA. Most of the research till date has been focused on describing gut bacterial components in RA. Studies on gut mycobiome and virome components in RA are relatively new and burgeoning field. Given the paucity of mycobiome or virome specific studies in RA, this review, discusses the recent findings on alterations in gut bacterial, fungal, and viral components as well as their role in regulating the spectrum of immune-pathogenic events occurring in RA which might be explored in future as a potential therapeutic target. Further, we provide an overview on inter-kingdom interactions between bacteria, fungi, and viruses in RA. The current understanding on gut microbiota modulation for managing RA is also summarised.